A STUDY OF THE APPLICATION OF DICTOGLOSS FOR VISUAL, AUDITORY, AND KINESTHETIC (VAK) STUDENTS IN ENGLISH LANGUAGE LEARNING - Yan Imam Santoso; Sainyakit, Paulus; Bagiya, Bagiya; Sugiharto, Prasetyawan Aji; Najib, Muhammad Reza Ainun (LPPM STBA Pontianak, 2025)
The method of English learning has been developed a lot. This allows teachers to choose a suitable method to apply in class. Meanwhile, students’ characters and learning models differ from one another. Many teachers do not pay attention to this in classroom learning. This research aims to examine the Dictogloss method for Visual, Auditory, and Kinesthetic students as an optimization of English language learning. This mixed methods research uses questionnaires, tests, interviews, and observations. This research uses pre-tests and post-tests as a tool to measure student development before and after treatment which is assessed quantitatively. The questionnaire was used to determine the sample's learning style, while interviews and observations were used as further research to examine more deeply the use of dictogloss for visual, auditory, and kinesthetic students. From this research, it was found that the dictogloss method can be effectively applied to English language learning characterized by visual, auditory, and kinesthetic learning styles. It's just that several things need to be considered in its application, such as the use of videos, audio recordings, and products produced to facilitate students' learning characteristics. So from this research, it can be concluded that dictogloss can be applied to English language learning with the characteristics of visual, auditory, and kinesthetic learning styles.